2022
DOI: 10.1155/2022/5058121
|View full text |Cite
|
Sign up to set email alerts
|

Targeting COPD with PLGA-Based Nanoparticles: Current Status and Prospects

Abstract: Chronic obstructive pulmonary disease (COPD) is pulmonary emphysema characterized by blockage in the airflow resulting in the long-term breathing problem, hence a major cause of mortality worldwide. Excessive generation of free radicals and the development of chronic inflammation are the major two episodes underlying the pathogenesis of COPD. Currently used drugs targeting these episodes including anti-inflammatory, antioxidants, and corticosteroids are unsafe, require high doses, and pose serious side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…The third-most common cause of mortality worldwide is a dangerous lung condition called chronic obstructive pulmonary disease (COPD) [ 53 ]. The current treatment of COPD mainly uses anti-inflammatory, antioxidant, and corticosteroid drugs, but the process of application requires higher doses and serious adverse effects [ 54 ]. Small molecule heat shock protein α,β-crystallin (HSPB5) is an extracellular protein with anti-inflammatory properties in a majority of inflammatory models [ 55 ].…”
Section: The Applications Of Plga To Biomedical Researchmentioning
confidence: 99%
“…The third-most common cause of mortality worldwide is a dangerous lung condition called chronic obstructive pulmonary disease (COPD) [ 53 ]. The current treatment of COPD mainly uses anti-inflammatory, antioxidant, and corticosteroid drugs, but the process of application requires higher doses and serious adverse effects [ 54 ]. Small molecule heat shock protein α,β-crystallin (HSPB5) is an extracellular protein with anti-inflammatory properties in a majority of inflammatory models [ 55 ].…”
Section: The Applications Of Plga To Biomedical Researchmentioning
confidence: 99%
“…[105][106][107] Due to its hydrophobicity, biocompatibility, thermoplasticity, easy modification of surface characteristics, adjustable biodegradation rate, and mechanical properties, it has been extensively studied and utilized in drug delivery and tissue engineering. [108][109][110][111][112][113] Studies have shown that PLGA has weak cell adhesion and its acidic degradation products are likely to cause inflammatory responses, 103,114,115 both of which are not conducive to endothelialization and tissue regeneration. However, the hydrophilicity of PLGA can be achieved by attaching different functional groups to modify its surface characteristics, thus improving the interaction with cells and tissues.…”
Section: Poly(lactic-co-glycolic Acid)mentioning
confidence: 99%
“…PLGA is a copolymer composed of PLA and PGA, which can be hydrolyzed and degraded into glycolic acid or lactic acid, and eliminated in the form of H 2 O and CO 2 under physiological conditions within a few months 105–107 . Due to its hydrophobicity, biocompatibility, thermoplasticity, easy modification of surface characteristics, adjustable biodegradation rate, and mechanical properties, it has been extensively studied and utilized in drug delivery and tissue engineering 108–113 . Studies have shown that PLGA has weak cell adhesion and its acidic degradation products are likely to cause inflammatory responses, 103,114,115 both of which are not conducive to endothelialization and tissue regeneration.…”
Section: Application Of Biodegradable Polymers In Absorbable Cardiac ...mentioning
confidence: 99%
“…Loss of effectiveness of polymer-coated medicinal compounds has been linked to the existence of antipolymer antibodies [155]. Improved targeting efficiency and decreased off-target effects can only be achieved by adjusting the PLGA NP encapsulation of miRNAs [156].…”
Section: Periodontal Regenerationmentioning
confidence: 99%